EFEKTIVITAS PELAKSANAAN PELAYANAN PENDAFTARAN NOMOR POKOK WAJIB PAJAK (NPWP) PRIBADI MELALUI SISTEM E-REGISTRATION (Studi Pada Kantor Pelayanan Pajak Pratama Kota Kupang) - Laluma, Adi Putra M.; Mau, Alfred Omri Ena; Oktavianto, Aspri Budi (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to analyze the effectiveness of the implementation of personal Taxpayer Identification Number (NPWP) registration services through the E-Registration system at the Kupang City Pratama Tax Service Office. Along with the development of information and communication technology, the Directorate General of Taxes has implemented the E-Registration system as a form of modernization of tax administration. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study indicate that the E-Registration system provides convenience and efficiency, but is not yet fully optimal because there are still obstacles to technical understanding from the community and uneven infrastructure. This study shows that the use of technology in public services is positively related to increased taxpayer compliance and satisfaction.